Victorian Ideologies in Contemporary British Cultures

Privacy-friendly User Location Tracking with Smart Devices: The BeaT Prototype - Betzing, Jan H; Niemann, Marco; Berendes, Carsten Ingo (Human Practice. Digital Ecologies. Our Future. - Tagungsband der 14. Internationalen Tagung Wirtschaftsinformatik (WI 2019))

Empowering Network Service Developers: Enhanced NFV DevOps and Programmable MANO - Soenen, Thomas; Tavernier, Wouter; Peuster, Manuel; Vicens, Felipe; Xilouris, George; Kolometsos, Stavros; Kourtis, Michail-Alexandros; Colle, Didier (IEEE Communications Magazine)

Introducing Automated Verification and Validation for Virtualized Network Functions and Services - Peuster, Manuel; Schneider, Stefan Balthasar; Zhao, Mengxuan; Xilouris, George; Trakadas, Panagiotis; Vicens, Felipe; Tavernier, Wouter; Soenen, Thomas; Vilalta, Ricard; Andreou, George; Kyriazis, Dimosthenis; Karl, Holger (IEEE Communications Magazine)

A high dynamic range optical detector for measuring single photons and bright light - Tiedau, Johannes; Meyer-Scott, Evan; Nitsche, Thomas; Barkhofen, Sonja; Bartley, Tim; Silberhorn, Christine (Optics Express)

Can stimuli improve business model idea generation? Developing software-based tools for business model innovation - Szopinski, Daniel (Proceedings of the ACM Creativity & Cognition)
A business model describes the mechanisms whereby a firm creates, delivers, and captures value. Following the steadily growing interest in business model innovation, software tools have shown great potential in supporting business model development and innovation. Yet, understanding the cognitive processes involved in the generation of business model ideas is an aspect of software design-knowledge that has so far been neglected. To investigate whether providing stimuli – in this case, brainstorming questions – can enhance individual creativity in this context, we conduct an exploratory experiment with over 100 participants. Our study is the first to systematically investigate the process of idea generation using a software-based business model development tool with stimuli. Our preliminary findings have the potential to support the future development of business model development tools and to refine the research design used to evaluate such tools.
Keywords: Business model innovation; idea generation; cognitive stimuli; business model development tools; experiment; creativity support system

Squaring the circle: Business model teaching in large classroom settings - Szopinski, Daniel (Journal of Business Models)
Business model innovation is typically taught in small seminars at universities. Teaching this intrinsically task-oriented subject to a large number of students is a challenge. In this paper we address this challenge by proposing an experiential and interactive approach to teaching business models in a large classroom setting.
Keywords: Business model teaching; peer assessment; experiential learning

Strong nonlinear optical response from ZnO by coupled and lattice-matched nanoantennas - Protte, Maximilian; Weber, Nils; Golla, Christian; Zentgraf, Thomas; Meier, Cedrik (Journal of Applied Physics)

Secular stagnation? Is there statistical evidence of an unprecedented, systematic decline in growth? - Fritz, Marlon; Gries, Thomas; Feng, Yuanhua (Economics Letters)

On-the-fly Usability Evaluation of Mobile Adaptive UIs through Instant User Feedback - Yigitbas, Enes; Jovanovikj, Ivan; Josifovska, Klementina; Sauer, Stefan; Engels, Gregor (Proceedings of the 17th IFIP TC.13 International Conference on Human-Computer Interaction (INTERACT 2019))